Morphological, yield, and nutritional characteristics of Chicory (Cichorium intybus L.) and Plantain (Plantago lanceolata L.) according to cutting interval in Peruvian Andes - Ysai Paucar; Saida Tecsi-Taipe; Luis H. Zagaceta-Llanca; Misael Rodríguez; Tony Vargas; Waldir Tarifa; Yolvi López-Mendoza; José Américo Saucedo-Uriarte; Héctor V. Vásquez; Ives Yoplac; Biviana Aquino; Flor L. Mejía (My University, 2026)
In Peru, the high Andean regions made up of grasslands are important for the sustainability of local systems. Improving and promoting the sustainability of forage production and quality allows producers to be resilient in the face of constant environmental changes. In this study, the morphological characteristics (plant height, leaf length and width), yield (fresh and dry matter) and nutritional characteristics [ash, ether extract, crude protein (CP), crude fiber, neutral detergent fiber (NDF), acid detergent fiber (ADF), in vitro digestibility of dry matter (IVDMD), nitrogen-free extract (NFE) and gross energy] of Cichorium intybus L. and Plantago lanceolata L. were evaluated, according to the cutting interval. Six experimental plots were implemented, three per species in each of C. intybus and P. lanceolata . An analysis of variances under a linear mixed model was performed of morphological and yield characteristics, including the cutting interval (28, 35 and 42 days), and the harvest (1, 2, 3 and 4 harvests) as fixed effects, while the plants were considered as a random effect. Tukey’s multiple comparisons test (p < 0.05) was used to group the results by species using R software. The number of leaves in C. intybus and P. lanceolata were higher at a cutting interval of 42 days of age and in the third and fourth harvest (p<0.05). The dry matter yield of C. intybus and P. lanceolata at 42 days was higher than that of the 28 and 35 days cut, with values of 1645 kg/ha and 1545 kg/ha, respectability. The nutritional parameters of C. intybus and P. lanceolata varied significantly according to harvest age (p<0.05). Ash, CP, NDF and ADF decreased, while IVDMD and NFE increased according to age. The CP concentration was 20.84% at 28 days, 18.99% at 35 days and 17.82% at 42 days in C. intybus and 19.29% at 28 days, 17.80% at 35 days and 15.17% at 42 days, while the IVDMD increased from 88.5% to 94.00% in C. intybus and 77.82% to 88.65% in P. lanceolata . Harvest age is key to optimizing yield and quality of C. intybus and P. lanceolata in high Andean livestock systems.
Keywords: Dry matter; Neutral Detergent Fiber; Forage; Biology; Yield (engineering); Mathematics; Fiber; Agronomy; Gram; Animal science; Botany; Fodder; Dry weight; Horticulture; Production (economics); Linear relationship; Organic matter; Degree (music); Dry matter; Neutral Detergent Fiber; Forage; Yield (engineering); Fiber; Gram; Life Sciences Agricultural and Biological Sciences Food Science Seed and Plant Biochemistry; Life Sciences Agricultural and Biological Sciences Plant Science Phytochemistry and Biological Activities; Life Sciences Agricultural and Biological Sciences Plant Science Ethnobotanical and Medicinal Plants Studies